Exploring the theology of resilience: Lessons from the Psalter for the South African context - Mokhutso, Jacob (Stellenbosch Theological Journal, 2023)
This article is a reflection on the theology of resilience using the book of Psalms, reading specifically from Psalm 137. The Psalmist seems to be addressing a few challenges, with which the Israelites were struggling at that time. First, there is the issue of anomie, where everything was crumbling around them, and disorder was the order of the day. Secondly, the Israelites were bothered by the historical memory of their past – as they remembered Jerusalem. Thirdly, the Israelites wondered how they could sing a song of the Lord in a strange place that was seemingly hostile and ungodly. Thus, the article uses these three challenges to reflect on the current situation within the South African context, by using the Psalter. To further engage this psalm, form-critical method, derived from a German word Formgeschichte which means “form-history” is used as a methodology. The article concludes with some challenges taken from the Psalter for the South African populace.